Higher school infrastructure as an object of management - Yu. V. Kotelevskaya (Вестник университета, 2023)
In modern conditions, search for an ideal combination of resources to meet needs of society with maximum benefit for the participants is becoming a key task of the modern economy. This is provided by the infrastructure which is a space that allows for material and non-material resources to move freely and ensures the achievement of the intended goals. In this regard, the infrastructure is a link, a service subsystem that provides vital activity of the system itself and its survival in the market. The article analyses the key indicators, characterising the infrastructure of higher education. The patterns, providing both positive and negative trends in the development of higher education, are revealed.Among the key factors that require close attention of both theoretical and practical economists are the factors that describe the decline in demand for higher education. This is the position of students and employees of higher school organisations.